2000
DOI: 10.1159/000016610
|View full text |Cite
|
Sign up to set email alerts
|

Socio–Economic and Behavioural Risk Factors for Tooth Loss from Age 18 to 26 among Participants in the Dunedin Multidisciplinary Health and Development Study

Abstract: Objective: To determine the risk factors associated with tooth loss between the ages of 18 and 26. Methods: Dental examinations at ages 18 and 26 were conducted on Study members in the Dunedin Multidisciplinary Health and Development Study, and sociodemographic and dental service use data were collected using a self–report questionnaire. At age 15, an estimate of socio–economic status (SES) for each Study member had been obtained by classifying the occupation of the male parent. A case of tooth loss was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 10 publications
3
74
1
6
Order By: Relevance
“…Dental examination methods used at each assessment have been previously reported; [31][32][33][34][35][36][37] methods relevant to the current investigation are summarised below.…”
Section: Methodsmentioning
confidence: 99%
“…Dental examination methods used at each assessment have been previously reported; [31][32][33][34][35][36][37] methods relevant to the current investigation are summarised below.…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers reported socio-economic inequalities were related to oral health loss. [15][16][17][18] The perceptions about dental disease of the respondents were 97.0% and only 3.0% respondent did not have idea about dental diseases.The respondents believe that improper cleaning of teeth and mouth 64.94%, taking of excessive sweets 21.64% and residual food in the oro-dental cavity 13.40% are responsible for dental diseases. Bad habit like mouth breathing 8.0%,tongue thrusting 1.0%, lip biting 3.0%, pencil biting 12.0% and Brushing 13.0% observed among the respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Bad habit like mouth breathing 8.0%,tongue thrusting 1.0%, lip biting 3.0%, pencil biting 12.0% and Brushing 13.0% observed among the respondents. Some study revealed that Dental and oral health are affected by diet and certain aspects of lifestyle [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations